2001
DOI: 10.1093/jac/48.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Elution characteristics of vancomycin, teicoplanin, gentamicin and clindamycin from calcium sulphate beads

Abstract: The in vitro release of vancomycin, teicoplanin, gentamicin and clindamycin from biodegradable calcium sulphate (CaSO(4)) carrier beads is described. All antibiotics showed prolonged release from the carrier beads, which was elevated during the first 24 h, with peak levels exceeding 2500 microg/bead. Doubling the antibiotic load of the beads revealed a more prolonged elution and a two-fold increase in antibiotic release. Local carrier-associated antibiotic treatment with CaSO(4) beads may prove to be effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 6 publications
2
65
0
4
Order By: Relevance
“…Also, the SEM data demonstrate the potential for eluting materials to be a nidus for infection and biofilm formation once antibiotic concentrations fall below bacterial MBCs and, therefore, emphasize the benefit of absorbable substrates. Studies have shown complete absorption of highpurity calcium sulfate within 4 to 6 weeks when combined with effective management of penile implant infection and of osteomyelitis (25,(40)(41)(42), indicating potentially wide-ranging benefits in the management of PIs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the SEM data demonstrate the potential for eluting materials to be a nidus for infection and biofilm formation once antibiotic concentrations fall below bacterial MBCs and, therefore, emphasize the benefit of absorbable substrates. Studies have shown complete absorption of highpurity calcium sulfate within 4 to 6 weeks when combined with effective management of penile implant infection and of osteomyelitis (25,(40)(41)(42), indicating potentially wide-ranging benefits in the management of PIs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used for decades to fill bone cavities resulting from disease, trauma, or surgery (11). It was recently shown to be potent in vitro for the release of vancomycin, teicoplanin, gentamicin, and clindamycin (15). The antimicrobial applied in such an elution system should be active against the most commonly involved pathogens of chronic bone infections, namely, methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (CoNS) (5).…”
mentioning
confidence: 99%
“…Any new delivery vehicle should be versatile, since elution rate depends upon the interaction of carrier and antibiotic 23,24 and since emerging bacterial resistance is causing physicians to reconsider traditional antibiotic therapies. 20,21,[25][26][27][28] We demonstrated that amikacin, gentamicin, or vancomycin can be delivered from the calcium sulfate dihydrate FAST pellets with effective dissolution and elution profiles.…”
Section: Discussionmentioning
confidence: 99%
“…At 1,4,8,12,24,36,48,72,96,120, and 144 h, pellets were removed, oven dried at 378C for 1 h, and weighed. The pellets were then reimmersed in fresh DI water.…”
Section: Dissolution Testingmentioning
confidence: 99%
See 1 more Smart Citation